Belonging and isolation in the Hellenistic world - Ager, Sheila L., 1956-; Faber, Riemer A. (Phoenix. Supplementary volume ;, 2013)
With a range of social, artistic, economic, political, and literary perspectives, the contributors provide a lively exploration of the tensions and opportunities of life in the Hellenistic Mediterranean.